2019
DOI: 10.5897/jen2019.0230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neem leaf extracts on Lepidopteran pest species attacking Solanum macrocarpon L. (Solanaceae) in southern Togo

Abstract: Lepidopteran pests cause considerable damage to Solanum macrocarpon Linnaeus (Solanaceae). Their control by the use of botanical extracts is a promising alternative to improper use of chemical insecticides. The objective of this study was to evaluate the effects of three doses of leaf extract of the neem tree, Azadirachta indica Adrien-Henri de Jussieu (Meliaceae) against Lepidopteran pest species that attack S. macrocarpon L. in southern Togo. The experimental design used for the study was randomized complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These results agree with the discoveries by Anyim et al [5] which showed that insecticidal application significantly increased yields of different crops. Abla & Seth [16] found that yield of Solanum macrocarpon plants sprayed with medium and high doses of the neem leaf extract were higher than those plants sprayed with the synthetic insecticide (Cydim Super). In this study, both neem bio-pesticide and synthetic insecticides were found to be effective in controlling the FAW.…”
Section: Laboratory Evaluation Of Neem Bio-pesticide and Synthetic In...mentioning
confidence: 99%
See 1 more Smart Citation
“…These results agree with the discoveries by Anyim et al [5] which showed that insecticidal application significantly increased yields of different crops. Abla & Seth [16] found that yield of Solanum macrocarpon plants sprayed with medium and high doses of the neem leaf extract were higher than those plants sprayed with the synthetic insecticide (Cydim Super). In this study, both neem bio-pesticide and synthetic insecticides were found to be effective in controlling the FAW.…”
Section: Laboratory Evaluation Of Neem Bio-pesticide and Synthetic In...mentioning
confidence: 99%
“…Bio-pesticides are usually considered to be more target-specific and inherently less toxic than synthetic insecticides hence limiting their impact on non-target species, such as other insects, birds and mammals. They usually are biodegradable in the natural environment, thus reducing exposure to environmental pollution and chances of developing insect resistance [16] . Among the botanical biopesticides currently under study for commercialization, neembased bio-pesticides are one of the least toxic to humans, shows very low toxicity to beneficial organisms and promising for the control of many insect pests [18] .…”
Section: Laboratory Evaluation Of Neem Bio-pesticide and Synthetic In...mentioning
confidence: 99%